Identification and molecular characterisation of Lausanne Institutional Biobank participants with familial hypercholesterolaemia – a proof-of-concept study (Swiss Medical Weekly, 2016)
AIMS: We aimed to identify familial hypercholesterolaemia mutation carriers among participants to the Lausanne Institutional Biobank (BIL). Our experimental workflow was designed as a proof-of-concept demonstration of the resources and services provided by our integrated institutional clinical research support platform. METHODS: Familial hypercholesterolaemia was used as a model of a relatively common yet often underdiagnosed and inadequately treated Mendelian disease. Clinical and laboratory information was extracted from electronic hospital records. Patients were selected using elevated plasma cholesterol levels (total cholesterol ≥7.5 mM or low-density lipoprotein cholesterol ≥5 mM), premature coronary artery disease status and age (18–60 yr) as main inclusion criteria. LDLR, APOB and PCSK9were analysed by high-throughput DNA sequencing. The most relevant mutations were confirmed by Sanger sequencing. RESULTS: Of 23 737 patients contacted by the BIL, 17 760 individuals consented to participate and 13 094 wished to be recontacted if there were findings requiring clinical action. Plasma cholesterol records were available for 5111 participants, of whom 94 were selected for genetic screening. Twenty-five of the tested patients presented with premature coronary artery disease while 69 had no such diagnosis. Seven heterozygous carriers of eight rare coding missense variants were identified. Three mutations were pathogenic (APOB p.R3527Q) or likely pathogenic (LDLR p.C27W, LDLR p.P526S) for hypercholesterolaemia, while the others were either benign or of unknown significance. One patient was a double heterozygote for variants APOB p.R3527Q and LDLR p.P526S. CONCLUSION: This work illustrates how clinical and translational research can benefit from a dedicated platform integrating both a hospital-based biobank and a data support team.